Laterality differences in elite ice hockey: An investigation of shooting and catching orientations - Puterman, J.; Schorer, J.; Baker, J. (Journal of Sports Sciences, 2010)
Little is known about the implications of motor asymmetries for skilled performers in dynamic, time-constrained, team-based activities such as ice hockey. Three studies were conducted to examine laterality differences in ice hockey. Study 1 investigated laterality distributions across three leagues of increasing calibre. Among skating players, skill level was related to changes in laterality patterns based on position, while a significant increase in the proportion of left-catching goaltenders was found across the levels of competition. Study 2 examined laterality differences through a 90-year retrospective analysis of player performance measures within an evolving system. Regression analysis indicated right shot preferences were associated with scoring more goals, while left shot preferences were related to assisting more goals. Among goaltenders, right-catching preferences were associated with an increased save percentage compared with left-catching goaltenders. In Study 3, player-goaltender shootout interactions revealed left shooters to be less successful against right-catching goaltenders. Results suggest ice hockey supports models of skilled perception, and provide new information in the area of laterality and strategic frequency-dependent effects in ice hockey.